VD_FINDINFO HC / 2019 / 618 vom 12. Juli 2019 - VD Tribunal cantonal (2019)
BAIL À LOYER, RÉDUCTIONEN GÉNÉRAL, TRANSACTIONACCORD, INTERPRÉTATIONSENS GÉNÉRAL | 259d CO, 260 CO, 308 al. 1 let. a CPC (CH)